Evidence-Based Practice (EBP) implementation among nursing students: Italian validation of S-EBPQ - Longo, Donato; Gili, Alessio; Ramacciati, Noemi; Morcellini, Rosita; Ramacciati, Nicola (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The use of Evidence-Based Practices in nursing has become essential for providing effective, safe, and personalized care. Nurses must learn the skill to use Evidence-Based Practice in universities, which represents the core of nursing education. Therefore, it appears necessary to evaluate students’ learning after the training period and to identify the strengths and obstacles to the implementation of Evidence-Based Practice put to use. This study aims to validate the Italian version of the Student Evidence Based Practice Questionnaire. Methods: The questionnaire was translated into Italian according to the World Health Organization guidelines. Content validation was carried out. A study was conducted on a sample of 119 students. The questionnaire was administered at four different times during the training period. The data were evaluated using the ANOVA test for repeated measures, Cronbach’s Alpha, and Pearson’s Correlation Coefficient. Results: The Content Validity Index demonstrated values greater than 0.8 in all items and overall. Cronbach’s Alpha showed values above 0.90 in the entire questionnaire. There was no correlation between the sex or age of the students and the score in the questionnaire. The mean scores gradually increased over the four administrations. Conclusions: The Student Evidence-Based Practice Questionnaire in the Italian version has proven to be a valid tool for assessing students’ approach to Evidence-Based Practice.